Reframing a 'theory of origin' of Malay architecture: a basis from the public realm - Jahn Kassim, Puteri Shireen; Abdul Majid, Noor Hanita; Mohd Nawawi, Norwina; Raja Abdul Kadir, Tengku Anis Qarihah (Universiti Kebangsaan Malaysia, 2019)
The origins of Malay architecture is typically linked to its vernacular past and vocabulary, primarily expressed in its residential timber traditions and arising from its detailed timber artisanship and constructions. Its constructional ingenuities had evolved a rich diverse language and grammar with its own localised aesthetics. Localized skills of the indigenous translate into structural and constructional marvels. This paper however, attempts to reframe a theory of origin of Malay architecture, extending from this basis and into the public realm of the Malay world. The roots of form of its traditional palaces and mosques represents the architectural and urban core of the regional past and thus can constitute a resource of expanding an ‘urban’ language. This paper reports on the mapping these palaces, using visual resources and reconstructions of surviving 17th century to the 1800s, to align these “early classicalised” and compact structures of different regions of Malay world, with shared expressions in their elevations and ornaments. Using these as departure points, the paper conceptualises an evolutionary ‘tree’ or geneanology which can account for the multiple and varied ethnocentric origins of the Malay world, argued as three main streams that had synthesised and mixed across time. The diverse public forms at different sites are linked to common archetypes in an attempt to re-enact a theory of origin. A qualitative approach taken in this research, focusing on aligning past ethnographic and anthropological findings of other researchers; including ethnolinguistic classifications and evolutions from different regionsargues to find geneanological roots and variants that explain the diversity. Using existing drawings, sketches on site visit, photography and literature reviewa, the paper selecta key regions as case studies, and the configurations of the public buildings are mapped in order to reframe into a theoretical taxonomy of origins. The taxonomy suggests a probable genealogical ‘tree’ of Malay architecture, from which its narrative can be reconstructed. Data in terms of elevational design, suggest five formal archetypes , which are the linear axial, layout configuration, deep plan projection, binuclear form, central and peristyle forms; and three ‘strands’ of ornamental character and stylisation. It proposes that a Classicalised language of Malay architecture, is possible which can mirror its ethnolinguistic and socio-political ‘urban’ origins, rather than stagnate into the hegemony of the ‘indigineous’; into a universal theory of beginning.